2023
DOI: 10.1186/s13045-023-01492-8
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and new technologies in adoptive cell therapy

Pengchao Zhang,
Guizhong Zhang,
Xiaochun Wan

Abstract: Adoptive cell therapies (ACTs) have existed for decades. From the initial infusion of tumor-infiltrating lymphocytes to the subsequent specific enhanced T cell receptor (TCR)-T and chimeric antigen receptor (CAR)-T cell therapies, many novel strategies for cancer treatment have been developed. Owing to its promising outcomes, CAR-T cell therapy has revolutionized the field of ACTs, particularly for hematologic malignancies. Despite these advances, CAR-T cell therapy still has limitations in both autologous and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 484 publications
0
12
0
Order By: Relevance
“…T-cell immunotherapy has been increasingly investigated in AML ( 16 ). Nevertheless, the redirection of pan CD3+ T cells to target leukemia blasts has demonstrated limited efficacy in clinical trials and is often accompanied with severe toxicity in patients with AML due to T-cell immune dysfunction ( 17 , 34 ). In vitro and mouse model studies have shown the cytotoxic effects of γδ T cells on AML cells ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…T-cell immunotherapy has been increasingly investigated in AML ( 16 ). Nevertheless, the redirection of pan CD3+ T cells to target leukemia blasts has demonstrated limited efficacy in clinical trials and is often accompanied with severe toxicity in patients with AML due to T-cell immune dysfunction ( 17 , 34 ). In vitro and mouse model studies have shown the cytotoxic effects of γδ T cells on AML cells ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a minor subset of lymphocytes, human γδ T cells account for approximately 2%–10% of CD3+ T cells in PB and exhibit non-major histocompatibility complex (non-MHC)-restricted recognition of tumor antigens ( 14 , 15 ). Upon activation in the periphery, γδ T cells exhibit remarkably diverse effector functions associated with immune response and a potent cytotoxic activity via elevated levels of CD107a expression and interferon (IFN)-γ cytokine production, granzyme B, and perforin secretion ( 16 , 17 ). Previously, we highlighted γδ T-cell-based immunotherapy as a highly promising strategy in cancer immunotherapy ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, engineered immune cell application also involves several limitations. Unavailability of suitable target, low antigen density, loss of antitumor activity due to exhaustion and poor infiltration possess challenges in CAR-T therapy [ 108 ]. Moreover, this therapy exhibits several adverse effects due to targeting antigens present in the normal tissues [ 109 ].…”
Section: Recent Clinical Advances In Breast Cancer Immunotherapymentioning
confidence: 99%
“…C-reactive protein along with various inflammatory cytokines are also elevated [ 111 ]. CAR-NK and CAR-M also exhibit several issues like limited proliferation capacity, insufficient infiltration, limited availibility, etc [ 108 ].…”
Section: Recent Clinical Advances In Breast Cancer Immunotherapymentioning
confidence: 99%
“…Adoptive cell therapy (ACT) is a promising immunotherapy targeting cancer cells by transferring specialized or engineered immune cells which are endowed with tumor-killing ability into a cancer patient ( 1 ). Among current ACTs implemented, chimeric antigen receptor (CAR) therapy becomes increasingly significant as T cells engineered with CAR (CAR-T) have shown clinical success in hematological malignancies in clinical settings owing to their remarkable anticancer abilities.…”
Section: Introductionmentioning
confidence: 99%